2001
DOI: 10.1074/jbc.m005206200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Structural Analysis of a Soluble Human Chorionogonadotropin Hormone-Receptor Complex

Abstract: Receptors for the luteotropin/human chorionogonadotropin hormone belong to the G-protein-coupled receptor family by their membrane-anchoring domains. They also possess a large extracellular domain (ECD) responsible for most of the hormone-receptor interactions. Structure-function studies identified several contacts between hormone and receptor ECD, but the precise topology of the complex is still unknown because of the lack of suitable heterologous expression means. Receptor ECDs exhibit leucine repeats and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Other examples in which the N-terminal domain of a GPCR binds ligand are the metabotropic glutamate receptor (33,34,51), the luteinizing hormone/human chorionic gonadotropin receptor (29), the follicle stimulating hormone receptor (28), the pituitary adenylate cyclase-activating polypeptide receptor (52), the PTH receptor (31), and the glucagon-like peptide-1 receptor (32), the last two also being members of the receptor subfamily to which the CRF receptor belongs. The glucagonlike peptide-1R, expressed and purified as a soluble protein in Chinese hamster lymphoblastoma cells, exhibited lower binding affinity compared with the native receptor, and lost activity after reduction of the disulfide bonds (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples in which the N-terminal domain of a GPCR binds ligand are the metabotropic glutamate receptor (33,34,51), the luteinizing hormone/human chorionic gonadotropin receptor (29), the follicle stimulating hormone receptor (28), the pituitary adenylate cyclase-activating polypeptide receptor (52), the PTH receptor (31), and the glucagon-like peptide-1 receptor (32), the last two also being members of the receptor subfamily to which the CRF receptor belongs. The glucagonlike peptide-1R, expressed and purified as a soluble protein in Chinese hamster lymphoblastoma cells, exhibited lower binding affinity compared with the native receptor, and lost activity after reduction of the disulfide bonds (32).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical characterizations of soluble ECD-1s include those of receptors for follicle stimulating hormone (28), luteinizing hormone/human chorionic gonadotropin (29), calcium (30), PTH (31), glucagon-like peptide-1 (32), and glutamate (33). The ECD-1 of the metabotropic glutamate receptor has also been characterized structurally by x-ray crystallography to 2.2-Å resolution (34).…”
mentioning
confidence: 99%
“…In addition, it has convincingly been demonstrated that purified ectodomains, truncated from their serpentine domains, do bind their cognate hormones with high affinity (Cornelis et al 2001, Remy et al 2001, Schmidt et al 2001. Very recently, crystallization of a complex between FSH and the ectodomain of the FSHR has provided the first direct structural evidence for the residues implicated in recognition specificity at the atomic level of resolution (Fan & Hendrickson 2005).…”
Section: The Binding Specificity Of Gphrs Is Clearly Encoded In Theirmentioning
confidence: 99%
“…These receptors have a rhodopsinlike transmembrane (TM) domain (Palczewski et al 2000, Themmen & Huhtaniemi 2000, Dias & Van Roey 2001, Ascoli et al 2002, Szkudlinski et al 2002 in common with the superfamily of GPCRs. In addition, they have a large N-terminal extracellular domain (ECD; 359-414 amino acid residues; homology , 40%), which conveys specific hormone binding to the receptors (Braun et al 1991, Cornelis et al 2001, Remy et al 2001. The TMs of individual glycoprotein hormone receptors appear to be functionally interchangeable and display high sequence homology (, 70%) between the different glycoprotein hormone receptors.…”
Section: Gonadotrophin Receptorsmentioning
confidence: 99%